A Tale of One City: The Devo Manc Deal and Its Implications for English Devolution. Issue 4 (20th July 2016) - Kenealy, Daniel
Abstract: On 2 November 2014 George Osborne stood in the impressive great council chamber of Manchester town hall and, flanked by the ten leaders of Greater Manchester's local authorities, announced a devolution deal for the city‐region. Greater Manchester would receive a significant package of powers over transport, housing, planning, skills, business support and welfare in exchange for creating new governance structures, including a directly elected mayor for the city‐region. This article explores the background to the Devo Manc deal, arguing that it is the product of both a long history of local government collaboration in Greater Manchester and George Osborne's desire for a sweeping restructure of English governance. It traces how the key decisions were taken quickly and by a small number of key officials. The article also identifies some flaws in Devo Manc and considers whether it is an appropriate model for other city‐regions in the UK.